PEMAKAIAN BRACE TERHADAP PENCEGAHAN PERKEMBANGAN KURVA LEBIH LANJUT PADA ADOLESCENT IDIOPATHIC SCOLIOSIS (AIS) ; Literature Review - Jihan Jaudah Putri (2020)
Objective: This study aims to examine some data from various sources used as material in making this review literature on the topic of use of brace to prevent further development in adolescent idiopathic scoliosis. Methods: Search for sources of literature, journals, articles, research results in several databases such as Google Schoolar, Science Direct, PEDro, PubMed and other journal sites using certain keywords in the period 2014-2020. From the results of the literature review review, it was found 3 articles and other journal sites that met the inclusion criteria. Journal quality assessment was assessed using the PEDro Scale method and analysis of 3 journals was carried out based on the suitability of the topic, study design used, number of samples, interventions used, and the results of each article. Results: After reviewing the literature as many as 3 articles showed that the use of braces with a longer duration of use can prevent the development of curves in adolescent idiopathic scoliosis. Conclusion: from the 3 journals obtained and analyzed, the conclusion is that the use of braces with a longer duration of use can prevent further curve development in adolescent idiopathic scoliosis.